Language and sexuality in Alfian Sa'at's English and Malay plays - Nabilah Syed Sultan (2011)
The content of Alfian Sa’at’s works in Malay and English are different. I say this in light of Sa’at’s Asian Boys Trilogy and two of his Malay plays in Bisik: antologi drama Melayu Singapura titled Anak Bulan Di Kampung Wa’ Hasan and Madu II. Though these plays thread on different subjects of discussion, ideas and controversies regarding Singapore’s nationalistic and cultural concerns, the one topic of exposition they have in common is sexuality. Many of Sa’at’s works in English and Malay dwell on the issues related to the Singapore’s nationalism, history and culture. Most of the time, the concerns presented in his English texts parallel his Malay text. This is Sa’at’s way of expanding his readership by reaching out to both his English and Malay speaking audience. Despite the similarity in content for several parts of the Asian Boys Trilogy, Anak Bulan and Madu II, Sa’at seems to be taking a different stand when displaying his ideas about sexuality.